Serological responses to the MVA-based JYNNEOS monkeypox vaccine in a cohort of participants from the Democratic Republic of Congo. Issue 50 (28th November 2022) - Priyamvada, Lalita; Carson, William C.; Ortega, Eddy; Navarra, Terese; Tran, Stephanie; Smith, Todd G.; Pukuta, Elisabeth; Muyamuna, Elisabeth; Kabamba, Joelle; Nguete, Beatrice U.; Likafi, Toutou; Kokola, Gaston; et al.
Highlight: JYNNEOS vaccination produces robust anti-orthopoxvirus antibody response. Naive vaccinees generate OPXV-specific IgM early after vaccination. IgG responses peak around 2 weeks after second vaccine dose. Titers wane at 2 years, and more rapidly in naïve vaccinees. Antibodies neutralize VACV and MPXV differently, but had similar rise from baseline. Abstract: The current worldwide monkepox outbreak has reaffirmed the continued threat monkeypox virus (MPXV) poses to public health. JYNNEOS, a Modified Vaccinia Ankara (MVA)-based live, non-replicating vaccine, was recently approved for monkeypox prevention for adults at high risk of MPXV infection in the United States. Although the safety and immunogenicity of JYNNEOS have been examined previously, the clinical cohorts studied largely derive from regions where MPXV does not typically circulate. In this study, we assess the quality and longevity of serological responses to two doses of JYNNEOS vaccine in a large cohort of healthcare workers from the Democratic Republic of Congo (DRC). We show that JYNNEOS elicits a strong orthopoxvirus (OPXV)-specific antibody response in participants that peaks around day 42, or 2 weeks after the second vaccine dose. Participants with no prior history of smallpox vaccination or exposure have lower baseline antibody levels, but experience a similar fold-rise in antibody titers by day 42 as those with a prior history of vaccination. Both previously naïve and vaccinated participants generate vaccinia virus and MPXV-neutralizing antibody in response to JYNNEOS vaccination. Finally, even though total OPXV-specific IgG titers and neutralizing antibody titers declined from their peak and returned close to baseline levels by the 2-year mark, most participants remain IgG seropositive at the 2-year timepoint. Taken together, our data demonstrates that JYNNEOS vaccination triggers potent OPXV neutralizing antibody responses in a cohort of healthcare workers in DRC, a monkeypox-endemic region. MPXV vaccination with JYNNEOS may help ameliorate the disease and economic burden associated with monkeypox and combat potential outbreaks in areas with active virus circulation.